Toward discovering a national identity for millennials: Examining their personal value orientations for regional, institutional, and demographic similarities or variations. (5th August 2019) - Weber, James; Loewenstein, Jeffrey; Lewellyn, Patsy; Elm, Dawn R.; Hill, Vanessa; Warnell, Jessica McManus
Abstract: Millennials are a powerful workforce group and are quickly becoming established business leaders, consumers, and investors. Yet, millennials are often described as a uniformly homogeneous generation, despite mounting evidence of variances across their private and workplace behaviors, attitudes and preferences, and personal values. This article examines the personal value orientations of millennials in the Unites States, reporting consistencies, variations, and contrasts based on a large sample drawn from seven diverse universities. Results of this article suggest more similarities across a national population of millennials than differences, suggesting a national identity among American millennials. Practical implications of our findings and future research are discussed.